NON-FORMAL EDUCATION IN THE CONTEXT OF MODERN TRENDS - Сурова, Дарья; Кульгильдинова , Тулебике; Сарсембаева , Арайлы; Семенова, Светлана (Pedagogy and Psychology, 2024)
In the modern world, specialists’ success depends on their ability to adapt to rapidly changing conditions in their lives and professional activities. Non-formal education is one of the ways to adjust educational trajectories to ensure continuous and flexible development tailored to learners’ individual needs and interests. This paper describes the findings of a study on the non-formal education model in higher education institutions. The study aims to develop a non-formal education model considering a three-element interaction: student, university, and external environment. Analytical and statistical information processing methods were used to review references and determine the needs of internal and external non-formal education consumers. The study’s findings justify the integration of non-formal education concepts into a traditional education system, that is, ensuring free academic activity, expanding learning options and trajectories, personal development, and forming a constantly growing need for acquiring knowledge and new competencies. Another result of the study is the identification of the key elements of non-formal education and the possibilities for its integration into the higher education system. The map of requests of each educational process participant has been made and some ways of non-formal education implementation have been shown in the example of NPJSC D. Serikbayev East Kazakhstan Technical University experience. The scientific and practical significance of the paper lies in a comprehensive overview of non-formal education scientific and educational potential, and a presentation of mechanisms for creating an educational environment to facilitate learners’ self-organization and self-development.